2002
DOI: 10.1021/np020014d
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenes from Ferula penninervis

Abstract: The ethyl acetate soluble extract of the dried roots of Ferula penninervis gave 17 new sesquiterpenes [15 of the guaiane-type, ferupennins A-O (1-15), and two of the eudesmane-type, 1alpha-hydroxy-2-oxo-5alpha,7beta,11betaH-eudesm-3-en-6alpha,12-olide (16) and penninervin (17)] and nine known sesquiterpenes. The structures of the new compounds were elucidated on the basis of spectroscopic evidence and X-ray analysis. The absolute configuration of ferupennin A (1) was determined by a modified Mosher method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…(9) were all present just like in 3, which established the a-orientation of HÀC (5), HÀC (8), HÀC (9), and Me (15), as well as the b-orientation of HÀC (4) and Me (14). The 1 H-and 13 C-NMR spectra of 1 and 2 displayed two sets of 15 C-atom signals in the ratio of 2 : 1, which indicated that the mixture was composed of two interconverting sesquiterpenoid isomers in the ratio of 2 : 1.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…(9) were all present just like in 3, which established the a-orientation of HÀC (5), HÀC (8), HÀC (9), and Me (15), as well as the b-orientation of HÀC (4) and Me (14). The 1 H-and 13 C-NMR spectra of 1 and 2 displayed two sets of 15 C-atom signals in the ratio of 2 : 1, which indicated that the mixture was composed of two interconverting sesquiterpenoid isomers in the ratio of 2 : 1.…”
mentioning
confidence: 74%
“…The NMR data indicated that 3 contained three AcO, one C¼O, an a,b-unsaturated g-lactone, three Me, two CH 2 , and four CH groups (including two oxygenated ones), as well as two quaternary C-atoms (including a dioxygenated one). Considering the characteristic 13 C-NMR signals at d(C) 9.0 (q), 14.1 (q), and 13.7 (q) due to Me(13), Me (14), and Me(15), two CH groups at d(C) 42.2 (d, C (4)) and 55.6 (s, C(5)), the sp 3 quaternary C-atom at d(C) 39.6 (C(10)), together with the a,b-unsaturated g-lactone group at d(C) 148.0 (s, C (7)), 132.6 (s, C (11)), and 170.4 (s, C (12)), and the noticeable dioxygenated quaternary Catom at d(C) 104.1 (C(6)), compound 3 was deduced to be a eudesmanolide containing a hemiketal function [3] [14] [15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 H-1 H correlations revealed its coupling to two vicinal protons which are characteristic for guaianolides with a 6,7-fused lactone. The spectrum further showed a signal due to exomethylene protons at δ = 4.10 (s, H-14) [8]. The signal at δ = 3.85 showed 1 H-1 H correlations to vicinal protons at δ = 3.38 (d, J = 12.0 Hz) and δ = 2.15 (ddd, J = 11.5; 10.1; 8.1 Hz) which could subsequently be assigned to H-5 and H-7, respectively.…”
Section: Resultsmentioning
confidence: 99%